Effects of high altitude hypoxia on left ventricular systolic time intervals in man. Issue 3 (March 1975) - Balasubramanian, V; Kaushik, V S; Manchanda, S C; Roy, S B
Abstract : Effects of high altitude hypoxia on systolic time intervals were examined in 34 healthy men: 20 sea level residents studied at rest and at the end of 3 minutes steady isometric (handgrip) exercise at sea level and then serially for the first 5 days and on the tenth day, at an altitude of 3658 m, and I4 permanent residents at high altitude studied at high altitude. In the sea level residents there was a significant increase in the pre-ejection period (PEP), abbreviation of the left ventricular ejection time (LVET), both corrected for heart rate, and prolongation of the PEP/LVET ratio at high altitude. The maximum changes were seen on days 2 and 3; these parameters tended to approach sea level control values by the tenth day. The systolic time interval values of high altitude residents were similar to the control values of the sea level residents obtained at sea level but significantly different from the changes in the sea level values seen in the first 4 days at high altitude. It thus appears that while the high altitude residents do not show any left ventricular dysfunction as determined by systolic time intervals, healthy sea level residents when exposed to high altitude hypoxia show a significant depression of the left ventricular function for at least the first 4 days. This might be a contributing factor in the genesis of high altitude pulmonary oedema.